Optimering och analys av bromskraft för kontrollerade ballistiska landningar av drönare avsedda för sjöräddning - Ataie, Yalda; Kilander, Erik (My University, 2023)
The Swedish Sea Rescue Society (SSRS) has suggested conceptual development work on their presently used drone, specifically focusing on the powertrain configuration. The reason for this is to improve and develop the maneuvering and landing abilities of the drone. Many of the drones currently used have a wide range in areas of use, they have great maneuvering abilities that enable controlled landing- and starting runs. Good capabilities at varying weather conditions, energy efficiency and optimized aerodynamics are other examples of coveted characteristics, which is especially true for longer flights. The problem is that maneuvering and energy efficiency are two conflicting requirements that are both dependent on the aerodynamics as well as on the powertrain. The currently used drone is a fixed wing drone, with large wings and a pushing propeller that enable good flying abilities and high energy efficiency. The goal is to fly out at sea and take photographs of places where rescuing help is needed. This suggests that the drone should have the possibility to execute a ballistic landing, rather than a glide landing, which means that the drone is able to land in a controlled manner, on a boat or another predetermined spot. In order to achieve this new type of landing the drag force from the propeller is being used to reduce the speed of the drone, by reversing the direction of rotation. Previous thesis works based on the same idea have presented the final velocities and drag forces that the currently equipped drone can achieve. The conclusion from these thesis works is that vertical ballistic landings are in fact not possible if the currently used powertrain is not upgraded. The project also discusses tests regarding the evaluation of drag forces, which is done in a feasibility study containing information about each drone component, measuring tools, measuring system analysis and trial planning. The purpose of the tests is to verify the virtual simulations, which can be determined by judging whether or not the theoretically obtained values do in fact converge towards the measured values from the tests. Two dimensionally designed simulations have yielded simplified system characteristics used to visualize modeled trajectories. The result is that the powertrain needs to deliver a minimum of 12 Newtons worth of drag force, additional to the drag force from the air resistance, and is to take place during reversed direction of rotation. Furthermore, a suggested design of experiments is presented, containing particularly interesting factors and magnitude of effects on drag forces they provide. The planned tests are meant to focus on the relationship between current levels and resulting drag force, where a concrete desirable measured value of drag force is predetermined by performed calculations